2009
DOI: 10.1002/chem.200801803
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and Kinetic Properties of the Lanthanoids(III) and Various Divalent Metal Complexes of the Heptadentate Ligand AAZTA

Abstract: The heptadentate ligand 1,4-bis(hydroxycarbonylmethyl)-6-[bis(hydroxycarbonylmethyl)]amino-6-methylperhydro-1,4-diazepine (AAZTA) and its derivatives were recently reported to give stable complexes with Gd(3+) with superior efficiency as MRI contrast agents. Nevertheless, only preliminary data are available on the coordination behavior of this interesting ligand. In this work, thermodynamic and kinetic stability data are determined for the formation of complexes with AAZTA and the lanthanoid metal ions, and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
127
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(136 citation statements)
references
References 39 publications
1
127
0
1
Order By: Relevance
“…The Mn 2+ complex of a DO3A analog where an oxygen donor is substituted for one of the macrocyclic ring nitrogens also shows decreased stability likely due to the lower total basicity of the ligand. The ligand AAZTA, which does not belong to any of the traditional ligand categories, was explored recently as a manganese chelator and showed acceptable affinity toward Mn 2+ [84]. The absence of an inner-sphere water molecule in Mn(AAZTA) 2− motivated the development of derivatives with reduced denticity [83].…”
Section: Mn 2+ -Based Contrast Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Mn 2+ complex of a DO3A analog where an oxygen donor is substituted for one of the macrocyclic ring nitrogens also shows decreased stability likely due to the lower total basicity of the ligand. The ligand AAZTA, which does not belong to any of the traditional ligand categories, was explored recently as a manganese chelator and showed acceptable affinity toward Mn 2+ [84]. The absence of an inner-sphere water molecule in Mn(AAZTA) 2− motivated the development of derivatives with reduced denticity [83].…”
Section: Mn 2+ -Based Contrast Agentsmentioning
confidence: 99%
“…The rates of this type of transmetallation reactions were found to be inversely proportional to the stability constants of the complexes [225]. The kinetics of metal exchange reactions between Gd 3+ complexes of AAZTA, DTPA, and DTPA derivatives in the presence of excess Cu 2+ , Zn 2+ , or Eu 3+ have been investigated more recently [23,30,62,84,226]. Under these conditions, the exchange reactions are pseudo-first-order and the rates can be expressed by Equation (4.8), where k d is a pseudo-first-order rate constant and [Ln(L)] t is the total concentration of the complex:…”
Section: Inertness Of Complexes Of Open Chain Ligands (Edta Dtpa Anmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently the AAZTA derivatives (AAZTA = 1,4-bis(carboxymethyl)-6-[bis(carboxymethyl)]-amino-6-methyl-1,4-diazepane) [11] were proposed, showing a good compromise between higher metal hydration and a good thermodynamic and an excellent kinetic stability [12]. The AAZTA ligand is formed by a seven-membered ring with two endocyclic and one exocyclic nitrogen atoms and four carboxymethyl side arms, representing a novel intermediate family between the open chain DTPA and macrocyclic DOTA ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of r 1p has to be ascribed to the presence of two coordinated water molecules in the inner coordination sphere of the Gd(III) ion. Furthermore, it has been shown that Gd-AAZTA displays a very good stability (log K f = 20.2) [2] and very limited aptitude to transmetallation in the presence of Cu 2+ and Zn 2+ ions. The easy preparation of AAZTA ligand is another attractive property and several derivatives have been reported [3][4][5][6].…”
mentioning
confidence: 99%